Mapping research landscapes: a bibliometric and visual analysis of ketogenic diet interventions in liver health (2013–2024) - Wang, Yinglian; Lu, Qingliu; Ma, Hailin; Huang, Jing’an; Zhang, Bo; Qin, Yunyun; Feng, Zhongwen; Jin, Xuefeng (Frontiers in Nutrition, 2025)
ObjectiveBibliometric and visual analysis in the field of ketogenic diet (KD) on Liver Health from 2013 to 2024.MethodsWe retrieved the articles published between 2013 and 2024 from the Web of Science database and the Scopus database, and conducted the analysis using R software and VOSviewer software.ResultsThe number of publications in this field shows an increasing trend year by year. The United States leads in the number of published articles, followed closely by China, Italy, Japan, and Canada. Notably, the United States has also excelled in international collaboration, with institutions like Sapienza University of Rome and the University of California, San Francisco, actively engaging with other global institutions. Nutrients has the highest publication frequency, while Cell Metabolism leads in citations. Key researchers such as Crawford PA and Watanabe M have emerged, with prominent keywords including obesity, Metabolic Associated Steatosis Liver Disease, NAFLD, beta-hydroxybutyrate, and low carbohydrate diet, indicating the central themes and trends in KD related Liver Health research.ConclusionKD, a novel dietary therapy designed to induce physiological ketosis, is anticipated to achieve significant advances in liver health. Global interest in this approach is increasing, underscoring its potential as an emerging therapeutic trend. This study offers a thorough analysis of the current research landscape and key hotspots related to the KD in liver health, providing valuable insights for future investigations.